2013
DOI: 10.1371/journal.pone.0055731
|View full text |Cite|
|
Sign up to set email alerts
|

Root Exudation of Phytochemicals in Arabidopsis Follows Specific Patterns That Are Developmentally Programmed and Correlate with Soil Microbial Functions

Abstract: Plant roots constantly secrete compounds into the soil to interact with neighboring organisms presumably to gain certain functional advantages at different stages of development. Accordingly, it has been hypothesized that the phytochemical composition present in the root exudates changes over the course of the lifespan of a plant. Here, root exudates of in vitro grown Arabidopsis plants were collected at different developmental stages and analyzed using GC-MS. Principle component analysis revealed that the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
402
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(418 citation statements)
references
References 68 publications
11
402
1
4
Order By: Relevance
“…Recent studies have shown that root secretion of defense-related proteins is enhanced during flowering time (De-la-Pena et al, 2010), suggesting an involvement of plant roots in ARR. Similarly, Chaparro et al (2013) have shown that Arabidopsis roots release more phenolic-related compounds at later stages of life which might be correlated to defense strategies against pathogens as secondary metabolites are involved in plant immunity against bacterial and fungal pathogens (Rogers et al, 1996;Clay et al, 2009;Millet et al, 2010;An and Mou, 2011;Bednarek, 2012). Thus, there is a need to understand the influence of plant development on microbial associations that might occur naturally in the rhizosphere related to defense but also to other vital plant necessities such as nutrient acquisition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that root secretion of defense-related proteins is enhanced during flowering time (De-la-Pena et al, 2010), suggesting an involvement of plant roots in ARR. Similarly, Chaparro et al (2013) have shown that Arabidopsis roots release more phenolic-related compounds at later stages of life which might be correlated to defense strategies against pathogens as secondary metabolites are involved in plant immunity against bacterial and fungal pathogens (Rogers et al, 1996;Clay et al, 2009;Millet et al, 2010;An and Mou, 2011;Bednarek, 2012). Thus, there is a need to understand the influence of plant development on microbial associations that might occur naturally in the rhizosphere related to defense but also to other vital plant necessities such as nutrient acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence demonstrating the close ties root exudates have on the microbial composition of the rhizosphere is mounting (Broeckling et al, 2008;Badri et al, , 2013aMicallef et al, 2009b;Chaparro et al, 2012Chaparro et al, , 2013, whereby many chemicals present in root exudates act as substrates, chemotactic or signaling molecules to orchestrate changes in microbial composition (Shaw, 1991;de Weert et al, 2002;Jain and Nainawatee, 2002;Horiuchi et al, 2005;Bais et al, 2006;Badri and Vivanco, 2009;Neal et al, 2012;Badri et al, 2013a). Recently, it was reported that the composition of Arabidopsis root exudates change following a plant developmental gradient (Chaparro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 d, in vitro plants were washed (three times) in distilled water and transferred into distilled water for 3 d before collecting root exudates (10 plants per 50 mL in a Falcon tube; adapted from Chaparro et al, 2013). Root exudates were centrifuged (2500 g for 5 min) to remove cell debris and border cells, freeze-dried and weighed before use.…”
Section: Collection Of Root Exudatesmentioning
confidence: 99%
“…Also shifts in diversity and abundance of microorganisms (e.g. methane oxidizing bacteria) during rice growth have been observed (Eller and Frenzel, 2001;Dianou et al, 2012), which could be partially attributed to the shift in the quantity and quality of root exudates during the growth of rice (Badri and Vivanco, 2009;Chaparro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%